MANAJEMEN PERUBAHAN LEMBAGA PENDIDIKAN ISLAM DI ERA GLOBALISASI - Munir, Misbah; Zakiyah, Ermita (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
This article discusses the change management Institution of Islam in the Era of globalization. The existence of Islamic educational institutions now is faced with various challenges, namely the existence of the current globalization, development of science and technology and the flow of information that is always evolving and constantly growing fast. In this era of technological advancement could not be avoided because of advances in technology will run in accordance with the development of science. Each innovation was created to provide positive benefits to human life. The technology also provides a lot of convenience, as well as a new way of doing human activities. Humans also already enjoy many of the benefits brought by the technological innovations that have been produced in the last decade. An attempt looking for a new idea about change management in Islamic institution certainly is not easy, therefore the need for the support of all parties. An attempt looking for a new idea about change management in Islamic institution certainly is not easy, therefore the need for the support of all parties. MTsN 1 Malang is a madrasah that is able to manage the institution so that it is able to survive as a flagship school of Islam, considering the development of the religion of Islam which should be offset by means of an adequate education to educate the their students are tough, then it is very exciting to be disclosed further through this research, and it is indeed a very appropriate with the title of the study i.e. change management institution of Islam in the era of globalization.